The role of the right dorsolateral prefrontal cortex in the Tower of London task performance: repetitive transcranial magnetic stimulation study in patients with Parkinson's disease - Srovnalova, H; Marecek, R; Kubikova, R; Rektorova, I (Experimental brain research, 2012)
We studied whether one session of high-frequency repetitive transcranial magnetic stimulation (rTMS) applied over either the right or left dorsolateral prefrontal cortex would induce any measurable changes in the Tower of London spatial planning task performance in patients with Parkinson's disease (PD). Ten patients with PD (with no dementia and/or depression) entered the randomized, sham-stimulation-controlled study with a crossover design. Active and placebo rTMS were applied over either the left or the right dorsolateral prefrontal cortex (in four separate sessions) in each patient. The order of sessions was randomized. The Tower of London task was performed prior to and immediately after each appropriate session. The "total problem-solving time" was our outcome measure. Only active rTMS of the right dorsolateral prefrontal cortex induced significant enhancement of the total problem-solving time, p = 0.038. Stimulation of the left prefrontal cortex or sham stimulations induced no significant effects. Only rTMS applied over the right dorsolateral prefrontal cortex induced positive changes in the spatial planning task performance in PD, which further supports the results of functional imaging studies indicating the causal engagement of the right-sided hemispheric structures in solving the task in this patient population.
Keywords: Executive Function; funkční lateralita; Female; Parkinsonova nemoc; Neuropsychological Tests; Brain Mapping; Functional Laterality; ženské pohlaví; neuropsychologické testy; lidé; transkraniální magnetická stimulace; Problem Solving; Mental Status Schedule; mapování mozku; prefrontální mozková kůra; Prefrontal Cortex; Male; Aged; řešení problému; záznam o duševním stavu; Transcranial Magnetic Stimulation; lidé středního věku; senioři; mužské pohlaví; exekutivní funkce; Middle Aged; Parkinson Disease; Humans